Implementasi Keamanan Jaringan Menggunakan Intrusion Detection System (IDS) Pada PT. Mega Esa Farma - Tri Santoso; Veren Prisscilya (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2021)
In the current global era, Information Technology (IT) has developed rapidly, especially with the existence of an internet network that makes it easy to communicate and exchange data with other parties. Because of the easy access to this information, security issues have become a major focus in the world of computer networks. This causes a new problem that is important information or data can be used by parties who are not responsible for their own benefits. So that a network security system becomes an important aspect. PT. Mega Esa Farma is an industrial company engaged in the field of Pharmacy. This company is one of the many companies in Indonesian that has obstacles in network security, the absence of monitoring on a company’s computer network is very bad for data security. Therefore, we need a system that can be used to monitor and proctect the network from threats that will occur. By using the Intrusion Detection System (IDS) with snort to follow up on the generated snort alerts. A DDOS attack and port scanning attempt has been conducted on a computer that has a snort installed and the results are obtained that the snort is able to detect the attack and directly send alert to the administrator.